Is it all about religious faith? Exploring the value of contemporary pilgrimage among senior travelers. Issue 5 (4th May 2019) - Kuo, Chun-Min; Chen, Li-Hsin; Liu, Chia-Hao
ABSTRACT: This study explores the values of pilgrimage exhibited by senior travelers in Taiwan. We identify and explore both spiritual and social values by applying means-end chain theory and the laddering technique. This study investigates the hierarchical relationship among pilgrimage attributes, the consequences that senior pilgrims obtained, and the satisfaction of personal values as an ultimate goal. The clear links are found among attributes, consequences, and values with social interactions that are acquired by keeping in touch with friends, followed by spiritual succor and support that connects with supporting temples, praying, and vow redemption. These findings provide novel insights into pilgrimage literature.